Logistics education for business management students: A learning-doing and service-learning approach (2019)
This article develops a teaching methodology in logistics for students of business administration programs to solve real problems in companies and integrate the knowledge acquired in logistics management courses. The methodology integrates project management tools with the support of MSExcel and promotes the elaboration of managerial reports according to the requirements of working environments. The methodology generates high satisfaction in the students, to the extent that it allows them to know in depth the logistic system of a company, identifies opportunities for improvement and proposes solutions based on technical and economic aspects. Likewise, the methodology allows the students to have contact with the directives of a real company and supports the improvement of logistics processes based on qualitative and quantitative information. © Primrose Hall Publishing Group.